The Construction of Adverb of Time in Bima Language: Syntax Perspective - Umar, Umar (International Seminar on Austronesian Languages and Literature; Vol 9 No 1 (2021): PROCEEDINGS International Seminar on Austronesian Languages and Literature IX (ISALL IX), 2021)
The current study attempts to describe the pattern of the syntactic construction of adverb of time in Bima language. The research data are in the form of a simple sentence used by Bima ethnic. The data collection was carried out using the observation method.  Based on the data analysis, the results showed that (1) there were four adverbs of times used by Bima ethnic, namely; continuous, present, future, and past tense, and (2) the simple sentence pattern of adverb of time of Bima language consist of Subject (S) + Predicate (P) + Noun Phrase (NP) + Preposition Phrase (PP)